2001
DOI: 10.1103/physrevlett.87.227401
|View full text |Cite
|
Sign up to set email alerts
|

Long Lived Coherence in Self-Assembled Quantum Dots

Abstract: We report measurements of ultralong coherence in self-assembled quantum dots. Transient four-wave mixing experiments at 5 K show an average dephasing time of 372 ps, corresponding to a homogeneous linewidth of 3.5 microeV, which is significantly smaller than the linewidth observed in single-dot luminescence. Time-resolved luminescence measurements show a lifetime of the dot ground state of 800 ps, demonstrating the presence of pure dephasing at finite temperature. The homogeneous width is lifetime limited only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
167
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(173 citation statements)
references
References 21 publications
3
167
1
2
Order By: Relevance
“…We note that although pure dephasing does not play an important role in IFQDs [15,16], its manifestation has been reported in SAQDs [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We note that although pure dephasing does not play an important role in IFQDs [15,16], its manifestation has been reported in SAQDs [17].…”
mentioning
confidence: 99%
“…This behaviour also rules out the mechanism resulting from coupling to delocalized excitons, proposed in [5] for interface fluctuation QDs (IFQDs) since that mechanism will take the excitonic state out of the QDs and will give rise to totally different overall behaviour. This is not surprising since the energy confinement in SAQDs is much higher than that in IFQDs.We note that although pure dephasing does not play an important role in IFQDs [15,16], its manifestation has been reported in SAQDs [17].What could be the underlying mechanism? The lattice mediated dephasing model proposed in [18], showed that the RO amplitudes decrease with the laser intensity.…”
mentioning
confidence: 99%
“…This entailed a severe decrease in the dephasing time of the qubit, as the non-radiative decay from the excited state to the exciton ground state (necessary for our detection scheme to work) puts an upper bound in the coherence time of the exciton 26 . This upper bound is significant, since measured dephasing times for excitonic ground states are in the order of hundreds of picoseconds 22,23,24 while those for carefully chosen excited states (i.e. no further than approximately 20 meV apart from the corresponding ground state) range in the tens of picoseconds.…”
mentioning
confidence: 99%
“…[21][22][23][24] The laser driving strength, ⍀, is chosen such that population within the excited states in the 11 subspace is only 1%.…”
Section: Conditional Dynamics With Imperfect Detectorsmentioning
confidence: 99%